Evaluating Nurses’ Understanding of Lower Back Pain and Approaches for Physical Therapy - Hasan, Mahfoudh Falih; Khalaf , Firas Hadi; Mutashar, Mohammed Kadhim; Atiyah, Maher Abdul Ameer (Universitas Muhammadiyah Sidoarjo, 2024)
Low back pain (LBP) is a widespread condition negatively impacting quality of life and productivity. Nurses play a vital role in managing LBP, especially through the application of physiotherapy techniques. This study aimed to assess nurses' perception levels regarding LBP and physiotherapy exercises. A descriptive cross-sectional study was conducted in Basra hospitals between May and August 2024, involving 80 nurses. Data were collected using a 24-items structured questionnaire covering general perception and exercise therapy, rated on a 3-point Likert scale. Perception levels were categorized as poor, medium, or good. The majority of participants (62.5%) were female. Overall, 58% demonstrated medium perception, followed by 37% with good perception and 5% with poor perception. In part-specific analysis, 83% scored well in general perception, while 72% passed the exercise therapy section. The mean scores were 14.82 ± 3.62 and 13.70 ± 4.33, respectively. No significant associations were found between demographic variables and perception levels. The findings indicate a need for targeted educational programs to enhance nurses’ competence in physiotherapy-based LBP management. Highlights: More than half of the nurses (58%) demonstrated a medium perception level regarding lower back pain and physiotherapy management. Higher understanding was observed in general knowledge (83% passed) than in exercise therapy (72% passed). The study emphasizes the need for targeted educational programs to improve nurses’ competence in physiotherapy-based pain management.